“Everybody Against VD!” The Health League’s Wartime Film and Lecture Events - Moretto, Enrico (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2024)
The Second World War saw the Health League of Canada revive its campaign to combat syphilis and gonorrhea among Canadians, a task made urgent by the perceived need to secure moral and medical advantages for the dominion during a global conflict. While the league strongly supported public venereal disease education, it was also convinced that Canadians would benefit most from a hybrid “moral-medical” model of teaching that blended scientific information with moral instruction. By examining the content presented to audiences in film and lecture events — a staple of the organization’s wartime activities, which blended entertainment, health education, and moral instruction — it becomes clear that the advice the league extended to Canadians was intended to reassert the importance of morality to public health at a time when increasingly effective treatments for venereal disease lessened the impact of infection. For the league, sexual activity within the confines of heterosexual marriage was the only morally and medically tenable form sexuality could take; any other alternative endangered the bodies and minds of Canadians at a time when their nation needed them at their healthiest.